Digital Asset Management Transformation: Implementing RadioBOSS Automation and ElevenLabs AI at Radio Istara Surabaya - Harliantara, Harliantara; Sugeng Widiarto, Didik; Desary SW, Widya; Ishadi Fadillah, Reza (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
Traditional FM towers are no longer monuments of stability but have become relics. In a world dominated by on-demand streams, Radio Istara Surabaya (101.1 FM) chose a radical "survival pivot" over a slow death. This study dissects how they dismantled legacy workflows by grafting RadioBOSS automation onto ElevenLabs’ synthetic voice engine. We are not just looking at software; we are looking at a 100% leap in production efficiency through a 60/30 model where AI handles the "grunt work" and humans act as curators. This is a survival map for the "post-radio" era.